Microstructures, mechanical properties, and grease-lubricated sliding wear behavior of Cu-15Ni-8Sn-0.8Nb alloy with high strength and toughness - Jinjuan Cheng; Mincong Mao; Xueping Gan; Qian Lei; Zhou Li; Kechao Zhou (Friction)
Abstract Alloys used as bearings in aircraft landing gear are required to reduce friction and wear as well as improve the load-carrying capability due to the increased aircraft weights. Cu-15Ni-8Sn-0.8Nb alloy is well known for possessing good mechanical and wear properties that satisfy such requirements. In this study, the microstructure, mechanical properties, and grease-lubricated sliding wear behavior of Cu-15Ni-8Sn-0.8Nb alloy with 0.8 wt% Nb are investigated. The nanoscale NbNi3 and NbNi2Sn compounds can strengthen the alloy through the Orowan strengthening mechanism. A Stribeck-like curve is plotted to illustrate the relationship among friction coefficient, normal load, and sliding velocity and to analyze the grease-lubricated mechanism. The wear rate increases with normal load and decreases with sliding velocity, except at 2.58 m/s. A wear mechanism map has been developed to exhibit the dominant wear mechanisms under various friction conditions. When the normal load is 700 N and the sliding velocity is 2.58 m/s, a chemical reaction between the lubricating grease and friction pairs occurs, resulting in the failure of lubricating grease and an increase in wear.